Development of an MCNP assisted modelling software based on OpenCasCade. (2017) - Zhou, Qingguo; Sun, Hongyu; He, Shuan; Yang, Jiaming; Tian, Yanshan
Monte Carlo N-particle transport code (MCNP) is used to calculate the large multi-particle transport in complex three-dimensional (3D) geometry. INP (default name of MCNP input file) file is created by users to solve calculation problems. The manual creation of INP file for MCNP geometry model description is a huge task and mistakes could be easily made. MCNP Assisted Modelling Software (MAMS) proposed in this paper is developed on OpenCasCade geometry engine. It not only achieves the general functions of 3D modelling software, but also performs the conversion of CAD and MCNP models mutually. Furthermore, MAMS implements some advanced functions required by specific users, such as Auxiliary Plane Decomposition (APD), setting the scope of surfaces' number in INP file according to user input. MAMS utilises Standard for the Exchange of Product Model Data (STEP) database as the native storage. It contains two main parts: 3D modelling software and data conversion.